(untitled) (Research, Society and Development, 2022)
This study aimed to quantify and identify the waste produced and the sustainability actions developed in a Popular Restaurant in the city of Belo Horizonte - Minas Gerais. Data were collected from October 2018 to September 2019, and organic, inorganic and oil residues were quantified. Through the structured participant observation technique, the positive and negative actions of environmental sustainability carried out at Restaurante Popular were identified. In the period of one year, 30,721.9 kg of waste was produced, 86.1% of organic waste, 11.2% of inorganic residues and 2.7% of oil. In the unit, actions are carried out in favor of sustainability, such as segregation and proper disposal of waste, use of clean leftovers, donation of the oil used and monitoring of per capita, rest intake, disposal of hardwood and leftovers. It is concluded that although the volume of waste produced in The Popular Restaurant is high, there is awareness on the part of professionals who develop various initiatives in waste management collaborating with environmental preservation and meeting the premises recommended in the National Plan for Solid Waste.